Anterior anal sphincter repair can be of long term benefit: a 12-year case cohort from a single surgeon - Grey, Benjamin R (BioMed Central, 2007)
BACKGROUND: Early surgical results of anterior sphincter repair for faecal incontinence can be good, but in the longer term are often disappointing. This study aimed to determine the short and long term outcomes from anterior sphincter repair and identify factors predictive of long term success. METHODS: Patients who underwent anterior sphincter repair between 1989 and 2001 in one institution were identified. Postal questionnaires were sent to patients, which included validated scoring systems for symptom severity and quality of life assessments for faecal incontinence. Patient demographics and risk factors were recorded as were the results of anorectal physiology studies and endoanal ultrasound. RESULTS: Eighty-five patients underwent repair by one consultant. The length of follow up ranged from 1 to 12 years. Most patients (96%) had early symptom improvement postoperatively. Of the 47 patients assessed long term (≥ 5 years), 28 (60%) maintained this success. Significant improvements in quality of life were observed (P < 0.001). Neither patient, surgical nor anorectal physiology study parameters were predictive of outcome. CONCLUSION: There were no predictive factors of outcome success and no changes in anal manometry identified, however anterior sphincter repair remains worthwhile. Changes in compliance of the anorectum may be responsible for symptom improvement.